2018
DOI: 10.1111/ina.12520
|View full text |Cite
|
Sign up to set email alerts
|

Indoor thermal stratification and its statistical distribution

Abstract: Thermal stratification is established when warmer air rises and cooler air descends under thermal buoyancy. It occurs in indoor environment situations including large warehouse‐type buildings, buoyancy‐driven ventilated spaces with displacement, underfloor ventilation, and/or natural ventilation, and enclosure fires with hot smoke layer on top of cold air layer. This paper reports a recent study that thermal stratification of indoor environment follows the statistical Beta distribution so the vertical temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thermal stratification was a common phenomenon with warmer air rising and cooler air descending as a result of thermal buoyancy, so a vertical temperature gradient/stratification was established in commercial and residential buildings. 34 Wang 35 found that the indoor thermal stratification may follow a statistical distribution – the Beta distribution so the vertical dimensionless temperature distribution was the cumulative distribution function (CDF) of the Beta distribution. We used the same hypothesis in this investigation in order to address thermal environment of oscillating jet by mathematical regression.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal stratification was a common phenomenon with warmer air rising and cooler air descending as a result of thermal buoyancy, so a vertical temperature gradient/stratification was established in commercial and residential buildings. 34 Wang 35 found that the indoor thermal stratification may follow a statistical distribution – the Beta distribution so the vertical dimensionless temperature distribution was the cumulative distribution function (CDF) of the Beta distribution. We used the same hypothesis in this investigation in order to address thermal environment of oscillating jet by mathematical regression.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, imputation techniques are required to replace missing instances with plausible substitutes leveraging contextual patterns. As only 1.1% of observations had partial voids, basic median and mode replacement was applied for numerical and categorical attributes based on their distribution statistics [40]. Sophisticated methods are warranted for larger missing proportions.…”
Section: Data Cleaning and Missing Valuesmentioning
confidence: 99%